2004
DOI: 10.1159/000076003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Climacteric Symptoms with Herbal Formulas of Traditional Chinese Medicine

Abstract: Hormone replacement therapy (HRT) is not successful or is contraindicated for the treatment of climacteric symptoms in some patients. To investigate whether certain herbal formulas of traditional Chinese medicine (Kampo in Japanese) could be used as an alternative treatment, a longitudinal ‘before and after’ comparative study was carried out in 18 Japanese women, and the results were compared with those of 16 women who underwent HRT. Kampo improved all the climacteric symptoms. In contrast, improvement of cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Regarding kampo it was reported that saikokeishikankyoto was effective for depression in peri-and post-menopausal women [27]. It was also reported that keishibukuryogan, tokishyakuyakusan and kamishoyosan improved climacteric symptoms [28]. Furthermore, kamishoyosan was proved to possess an antidepressant-like effect at a behavioural and molecular level in rats [29].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding kampo it was reported that saikokeishikankyoto was effective for depression in peri-and post-menopausal women [27]. It was also reported that keishibukuryogan, tokishyakuyakusan and kamishoyosan improved climacteric symptoms [28]. Furthermore, kamishoyosan was proved to possess an antidepressant-like effect at a behavioural and molecular level in rats [29].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we are tempted to assume that keishi‐bukuryo‐gan may have an impact on the disposition of endogenous and/or exogenous oestrogens. A previous study reported that there was no significant change in the endogenous serum estradiol levels after long‐term treatment with keishi‐bukuryo‐gan in six postmenopausal female patients [7] . However, there are no available data on whether there is an improved efficacy and/or adverse events in relation to the interaction between keishi‐bukuryo‐gan and exogenous oestrogens, such as hormone replacement therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Many female patients are now using herbal medicines to relieve menopausal symptoms, such as hot flashes and night sweating [3,6] . In Japan, keishi‐bukuryo‐gan (Chinese name: Gui‐Zhi‐Fu‐Ling‐Wan) is one of the most frequently used Kampo medicines and it is widely accepted in Japan as an effective alternative treatment for hypermenorrhoea, dysmenorrhoea and menopausal symptoms [7,8] . The pharmacologically active ingredients of keishi‐bukuryo‐gan are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used for gynecological diseases [19,20]. There are some reports on climacteric symptoms [21] and improvement of luteal insufficiency [22]. These reports are interesting, as TS has been reported to improve memory disturbance in menopausal rats [7].…”
Section: Discussionmentioning
confidence: 99%